A Model Describing the Osmotic Coefficients and the Activities of Water for Electrolyte Solutions - Fang, Zheng (Asian Journal of Chemistry, 2011)
This work presents a model for thermodynamic properties of the uni-univalent electrolytic solutions based on the linear relation between the constructed dimensionless-thermodynamic potential for solvent and the newly defined probability-distribution function of water molecules. The model allows quantitative reproduction of the osmotic coefficients for the uni-univalent electrolytic solutions, especially for some hydroxides of alkali metals and monoacids such as NaOH, KOH, LiOH, HF, HCl, HBr, HI, HNO3 and H(HSO4), within experimental accuracy. A comparison is made of the results of the presented model with the Pitzer's equation.